One for the Money - Robinson, Julie Anne.; Heigl, Katherine; O'Mara, Jason; Sunjata, Daniel, 1971-; Leguizamo, John.; Shepherd, Sherri, 1967-; Reynolds, Debbie; Evanovich, Janet; Lions Gate Home Entertainment ([United States] : Lions Gate Home Entertainment, 2012)
Stephanie Plum is a bright, attractive, confident woman whose entire life has just taken a sudden turn, in the totally wrong direction. Newly divorced and recently laid off, the only work she can scrape up is a dead-end job at her sleazy cousin's bail bond office. But when her first big assignment involves tracking down an on-the-lam ex-flame, this tough-as-nails lady bounty hunter will be redefining the meaning of hot pursuit.
Keywords: Plum, Stephanie (Fictitious character) -- Drama; Women detectives -- Drama; Divorced women -- Drama; Feature films; Comedy films; Video recordings for the hearing impaired